2016
DOI: 10.1007/s40195-016-0432-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing on the Microstructure and Properties of In-situ Cu–Nb Microcomposite Wires

Abstract: The effects of annealing on microstructure, magnetoresistance, and hardness of an in situ Cu-Nb microcomposite wire have been investigated. Neither changes in microstructure nor hardness were found until 500°C. Particularly, microstructural change within the Nb films was observed in the annealed samples. The room-temperature magnetoresistivity was almost negligible, while magnetoresistivity at -196°C increased with magnetic field. At temperature above 500°C, recovery and recrystallization occurred, and both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…That is why the problem of thermal stability of Cu-Nb composites is of great importance. The loss of their strength at annealing is mostly associated with modification of the specific structure of Nb filaments in the copper matrix, namely, with transformation of ribbon-like filaments into bamboo-like ones, that is, their spheroidizing and coarsening [28][29][30]. In this regard, the microstructural investigation of composite at different annealing temperatures, which allows specifying the temperature of the beginning and end of softening after different true strains before the annealing, is of significant interest.…”
Section: Introductionmentioning
confidence: 99%
“…That is why the problem of thermal stability of Cu-Nb composites is of great importance. The loss of their strength at annealing is mostly associated with modification of the specific structure of Nb filaments in the copper matrix, namely, with transformation of ribbon-like filaments into bamboo-like ones, that is, their spheroidizing and coarsening [28][29][30]. In this regard, the microstructural investigation of composite at different annealing temperatures, which allows specifying the temperature of the beginning and end of softening after different true strains before the annealing, is of significant interest.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, high magnetic field (HMF) has been successfully applied to material design and productions [8][9][10][11][12]. The HMF not only significantly influences the liquid/solid solidification micro-/macro-structures for both ferromagnetic and non-ferromagnetic metals [13], but also a powerful tool to affect the crystallization process of amorphous alloy, texture formation of the crystallized phases [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The HMF not only significantly influences the liquid/solid solidification micro-/macro-structures for both ferromagnetic and non-ferromagnetic metals [13], but also a powerful tool to affect the crystallization process of amorphous alloy, texture formation of the crystallized phases [14][15][16][17]. The constant and strong magnetic field shows both magnetic forces and transmits highintensity energy to the atomic scale of matter without contact, thus changing the whole energy of the material phases and dynamic behavior of atomic arrangement, matching and migration [9,11,12,18,19]. Tsurekawa et al applied a 6 T magnetic field to a typical Fe 73.5 Cu 1 Nb 3 Si 13.5 B 9 alloy and concluded that the HMF increased the nucleation rate of α-Fe but hardly demonstrated any obvious effects on the grain size refinements during the crystallization process [20].…”
Section: Introductionmentioning
confidence: 99%
“…The quality of final metal product is largely dependent on the solidification structure that emerges during the initial casting [1][2][3][4]. A refined microstructure with reduced defects in as-cast billets yields improved properties in end products [5,6].…”
Section: Introductionmentioning
confidence: 99%